Medical performance and the 'inaccessible' experience of illness: an exploratory study. Issue 3 (26th July 2016) - Weitkamp, Emma; Mermikides, Alex
Abstract : We report a survey of audience members' responses (147 questionnaires collected at seven performances) and 10 in-depth interviews (five former patients and two family members, three medical practitioners) to bloodlines, a medical performance exploring the experience of haematopoietic stem-cell transplant as treatment for acute leukaemia. Performances took place in 2014 and 2015. The article argues that performances that are created through interdisciplinary collaboration can convey otherwise 'inaccessible' illness experiences in ways that audience members with personal experience recognise as familiar, and find emotionally affecting. In particular such performances are adept at interweaving 'objectivist' (objective, medical) and 'subjectivist' (subjective, emotional) perspectives of the illness experience, and indeed, at challenging such distinctions. We suggest that reflecting familiar yet hard-to-articulate experiences may be beneficial for the ongoing emotional recovery of people who have survived serious disease, particularly in relation to the isolation that they experience during and as a consequence of their treatment.